2014
DOI: 10.1016/j.apsb.2013.12.010
|View full text |Cite
|
Sign up to set email alerts
|

An aerosol formulation of R-salbutamol sulfate for pulmonary inhalation

Abstract: An aerosol formulation containing 7.5 mg of R-salbutamol sulfate was developed. The aerosol was nebulized with an air-jet nebulizer, and further assessed according to the new European Medicines Agency (EMA) guidelines. A breath simulator was used for studies of delivery rate and total amount of the active ingredient at volume of 3 mL. A next generation impactor (NGI) with a cooler was used for analysis of the particle size and in vitro lung deposition rate of the active ingredient at 5 °C. The anti-asthmatic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Many techniques for B. odoriphaga control have been investigated, including entomopathogenic nematodes [9][10][11], colored plates, and other methods that do not involve chemical pesticides [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Many techniques for B. odoriphaga control have been investigated, including entomopathogenic nematodes [9][10][11], colored plates, and other methods that do not involve chemical pesticides [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…41,42 The NGI is a high-performance cascade impactor for classifying aerosol particle into size fractions for testing inhaled drug delivery devices such as nebulizers. 43 Moreover, Spraytec is one of the most popular laser diffraction devices specically designed to address the unique requirements of aerosol and spray droplet characterization and provides real-time and accurate droplet measurement. [44][45][46] Consistent with the results of DR, TDD, and TED, we observed that Pari Boy SX (red) produced the lowest aerosol particle size of RIS among these ve nebulizers, suggested by the values of D 50 and MMAD.…”
Section: Discussionmentioning
confidence: 99%
“… 1 Asthma may also be classified as atopic (extrinsic) or nonatopic (intrinsic), where atopy refers to a predisposition toward developing type 1 hypersensitivity reactions. 2 , 3 Asthma is the clinical condition that may occur in adult and pediatric patients. For some children with asthma, their first asthmatic experience can be frightening – heavy wheezing, a tight chest, and shortness of breath can quickly catch their active, young bodies off-guard.…”
Section: Introductionmentioning
confidence: 99%